Molecular identification of a novel endophytic fungus Botryotrichum murorum associated with tomato in Iraq - ALAA A. AL-RIFAIE; MARWAN Y. AL-MAQTOOFI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Al-Rifaie AA, Al-Maqtoofi MY. 2025. Molecular identification of a novel endophytic fungus Botryotrichum murorum associated with tomato in Iraq. Biodiversitas 26: 2970-2977. Due to the economic importance of tomato crops in Iraq, this study was designed to investigate new endophytic fungal species related to Sordariomycetes (Ascomycota), a class known for its diverse ecological roles. From Al-Zubair region, which includes well-known farms of tomato and located in the South of Basrah Province in Iraq, a total of 35 cultivated vegetable tomato (Solanum lycopersicum) samples were collected. These samples were processed by cutting them into small pieces sized (5-6 mm) using sterile blades. Two isolation protocols, including the Solid Culture Method (SCM) and the Moist Culture Method (MCM), were employed for endophytic fungal isolation. The recovered endophytic fungi were purified, and axenic cultures of each isolated fungal species were then identified initially based on macro and micro-morphological features. For accurate taxonomy, molecular technique was utilized by genomic DNA extraction and PCR amplification of multigene sequences such as ITS (Internal Transcribed Spacers 1 and 2 including the 5.8S nrDNA), LSU (D1/D2 domains of the 28S nrDNA), RPB2 (partial RNA polymerase II second largest subunit gene), TEF-1? (translation elongation factor 1-alpha gene) and ?-tubulin (TUB2) gene were used for identification. Phylogenetic analysis showed the isolation of Botryotrichum murorum as a dominant endophytic fungal species. This species was reported for the first time as a novel isolation in the Iraqi mycobiota.